Early Inhibition of P-Selectin/P-Selectin Glycoprotein Ligand-1 Reduces Intimal Hyperplasia in Murine Vein Grafts through Platelet Adhesion - Tseng, Chi-Nan; Chang, Ya-Ting; Yen, Cih-Yi; Lengquist, Mariette; Kronqvist, Malin; Eriksson, Einar E.; Hedin, Ulf (Thrombosis and Haemostasis, 2019)
Inflammatory processes contribute to intimal hyperplasia (IH) and long-term failure of vein grafts used in bypass surgery. Leukocyte recruitment on endothelial cells of vessels during inflammation is regulated by P-selectin and P-selectin glycoprotein ligand-1 (PSGL-1), which also mediates the interaction between platelets and endothelial cells in vein grafts transferred to arteries. However, how this pathway causes IH in vein grafts is unclear. In this study, we used a murine model of vein grafting to investigate P-selectin-mediated platelet adhesion, followed by IH. On the luminal surface of the vein graft, leukocyte recruitment occurred mainly in areas with adhered platelets rather than on endothelial cells without adherent platelets 1 hour after vein grafting. Blockage of either P-selectin or PSGL-1 reduced platelet adhesion and leukocyte recruitment on the luminal surface of vein grafts. Inhibition of the P-selectin pathway in vein grafts significantly reduced platelet-mediated leukocyte recruitment and IH of vein grafts 28 days after surgery. The study demonstrates that functional blockage of the P-selectin/PSGL-1 pathway in the early inflammatory phase after vein grafting reduced leukocyte invasion in the vein graft wall and later IH development. The findings imply an attractive early time window for prevention of vein graft failure by manipulating platelet adhesion.
Keywords: vein graft; intimal hyperplasia; leukocytes; platelets; P-selectin